Promising practices for engaging families in STEM learning - Caspe, Margaret; Woods, Taniesha A.; Kennedy, Joy Lorenzo (Family, school, community, partnership issues., 2018)
The technology revolution has made it critical for all children to understand science, technology, engineering, and math (STEM) or risk being left behind. Promising Practices for Engaging Families in STEM Learning explores how families, schools, and communities can join together to promote student success in STEM by building organized and equitable pathways for family engagement across all of the settings in which students learn - including, schools, early childhood programs, homes, libraries and museums -from the earliest years through adolescence.This thought-provoking monograph includes three main sections with chapters from leading thinkers in the field:The first section provides the theoretical and research base for the importance of family engagement in STEM and draws out the challenges and opportunities that exist- from the transmission of adults' anxiety and lack of confidence in their own STEM skills, to inequalities in out-of-school learning opportunities, to biases and misconceptions about the kinds of STEM supports offered by families from low-income and immigrant homes.The second section builds on this research by presenting success stories, best practices, and approaches to engaging families in STEM.The final section focuses on how policies at the local, state, and federal level can support the promotion of family engagement in STEM.Taken together, the monograph shows that STEM is a powerful mechanism to connect, engage, and empower families.-STEM provides opportunities for parents and children to spend time together asking fun and meaningful questions that link in-and out-of-school learning.-STEM creates new experiences for families to co-construct and support learning with their children from the earliest years throughout formal schooling and onto college and career pathways.-STEM also presents possibilities for families to build confidence and agency in supporting children's interests; especially those families who might be marginalized because of their economic or language status, race, or culture.